Пластика з трипільських поселень Канівського Подніпров'я: нові надходження - Овчинников, Е.В. (Археологія і давня історія України, 2018)
Проаналізовано пластику трипільської культури, що походить з поселень Канівського Подніпров'я і зберігається у Наукових фондах Інституту археології НАН України. The analysis of plastics from Trypillian sites of the Dnipro River Kaniv region which is stored in the Scientific Repository of the Institute of Archaeology of the National Academy of Sciences of Ukraine is presented. Peculiarities of products are discussed with the maximum consideration of their features: technological, morphological, and stylistic. The technology of manufacturing the Kaniv plastics shows peculiarities distinguishing it among the products originating from the neighbouring western and eastern local formations. Anthropomorphic, zoomorphic, and ornithomorphic figures are distinguished, as well as plastic objects of other forms. Traditional forms and ornamentation were open for innovations within the general Trypillian plastic development. There were also new forms of anthropomorphic images, inherent exclusively to the Kaniv population. These are female figures with separately moulded legs connected by a bridge in the area of knees. Such figurines are found as imports at the settlements of neighbouring Trypillian local groups. Unique are realistic heads with almost portrait features and an anthropomorphic application on a vessel. Plastic, primarily anthropomorphic, reflects the mythological ideas of the early farmers which were based on ideas of fertility, fruitfulness, dualism, and rebirth.